The Role of Highly Active Antiretroviral Therapy (HAART) on Interleukin 17A (IL-17A) in Normotensive and Preeclamptic Black South African Women - Wendy N. Phoswa; Thajasvarie Naicker; Veron Ramsuran; Jagidesa Moodley (Hindawi Limited, 2020)
Introduction. Interleukin 17A has been implicated in the pathophysiology of both human immune deficiency virus and preeclampsia. This study evaluated serum levels of IL-17A based on pregnancy type, gestational age, HIV status, and duration of HAART. Material and Methods. A sample size of 250 was analysed: normotensives (n=150; N) and preeclamptics (n=100; PE). Normotensives were further stratified into HIV negative (n=90), HAART-acute (n=30), and HAART-chronic (n=30). The PE group was divided into early onset (n=50; EOPE) and late onset (n=50; LOPE). The EOPE and LOPE groups were subdivided into HIV negative (n=30), HAART-acute (n=10), and HAART-chronic (n=10). Analysis of IL-17A was performed using a multiple Bio-Plex immunoassay method. Results. Pregnancy type: the levels of IL-17A were increased in PE compared to N (P=0.0014). Gestational age: the levels of IL-17A were increased in EOPE compared to N group (P=0.0113). A significant increase in the levels of IL-17A in LOPE compared to N was observed (P=0.0063). HIV status: the levels of IL-17A were increased in PE compared to N (P=0.0114) and in EOPE compared to N groups (P=0.0071). HAART duration: the concentration of IL-17A was increased in HAART-chronic PE compared to N groups (P=0.0062). There was also an increase in the levels of IL-17A in EOPE compared to N (P=0.0029). Conclusion. The study demonstrates that IL-17A is involved in the pathophysiology of PE and that in the presence of HIV infection, chronic HAART administration predisposes women to the development of EOPE.